2012
DOI: 10.1038/ijo.2011.259
|View full text |Cite
|
Sign up to set email alerts
|

Children's binge eating and development of metabolic syndrome

Abstract: Background Binge eating predisposes children to excessive weight gain. However, it is unknown if pediatric binge eating predicts other obesity-associated adverse health outcomes. Objective The objective of this study was to investigate the relationship between binge eating and metabolic syndrome (MetS) in children. Method Children 5–12 y at high risk for adult obesity, either because they were overweight/obese when first examined or because their parents were overweight/obese, were recruited from Washingto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 39 publications
9
108
2
2
Order By: Relevance
“…Unhealthy food choices, including the ingestion of high trans-fat foods, are also known to be associated with serum levels of TG [36][37][38][39]. Binge eating disorder has been associated with the onset of adverse metabolic profile in other samples [40]. Although disordered eating behaviors such as binge eating episodes, eating rapidly or irregular meal patterns have been associated with increased fasting glucose levels, decreased glucose tolerance and elevated serum lipids [41][42][43], this relation has not been established for the postbariatric population thus far.…”
Section: Discussionmentioning
confidence: 97%
“…Unhealthy food choices, including the ingestion of high trans-fat foods, are also known to be associated with serum levels of TG [36][37][38][39]. Binge eating disorder has been associated with the onset of adverse metabolic profile in other samples [40]. Although disordered eating behaviors such as binge eating episodes, eating rapidly or irregular meal patterns have been associated with increased fasting glucose levels, decreased glucose tolerance and elevated serum lipids [41][42][43], this relation has not been established for the postbariatric population thus far.…”
Section: Discussionmentioning
confidence: 97%
“…26 Moreover, those with LOC eating are five times more likely to develop metabolic syndrome at 5-year follow-up, with changes in BMI only partially explaining this association. 27 However, it is unknown if youth with LOC eating have elevated inflammatory factors, which may contribute to the worsening metabolic components and increased cardiometabolic risk observed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found infrequent eating to be associated with higher circulating triglycerides [13,14]. Infrequent eaters also consistently show an increased caloric intake per EO, and binge eating behaviors have been previously linked to increased triglycerides [14,47]. Infrequent eaters have also shown increased visceral adipose tissue [14] and the accumulation of visceral adipose tissue has been positively associated with fasting insulin and triglycerides [14,59].…”
Section: ≤001mentioning
confidence: 74%
“…However, the vast majority of the eating frequency research, including this study shows a positive relationship between eating frequency and energy intake, which very well could be an artifact of under-reporting which is discussed below. It is also plausible that reduced eating frequency may result in eating behaviors that resemble binge eating which has been related to increases in metabolic disease parameters and adiposity measures [47]. Thus, much more research is needed to examine the exact mechanisms of how eating patterns impact satiety, hunger, and ad libitum dietary intake in free-living populations.…”
Section: ≤001mentioning
confidence: 99%